2013
DOI: 10.1063/1.4813763
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial effect on the ferromagnetic damping of CoFeB thin films with different under-layers

Abstract: Interfacial effects on magnetic properties are investigated for the as-deposited and annealed Co64Fe16B20 films with different under-layers (Cu, Ru, or Pd). The intrinsic Gilbert damping factor is inferred to be slightly lower than the obtained value of 0.007. We found that both the in-plane coercivity Hc and ferromagnetic resonance linewidth ΔHpp rely on the interfacial morphology. The Cu under-layer provides a rough surface, which offers an extra contribution to the ΔHpp. The surface roughness was greatly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…12,13 The observed values of a are consistent with the values reported in the literature. 15 Other analytical investigations were then carried out to look for a plausible cause for these changes in a and DH 0 , the parameters that represent magnetization dynamics. Figure 2 shows the normalized depth profiles of B, Fe, and MgO in S-I, S-R, and S-PO.…”
mentioning
confidence: 99%
“…12,13 The observed values of a are consistent with the values reported in the literature. 15 Other analytical investigations were then carried out to look for a plausible cause for these changes in a and DH 0 , the parameters that represent magnetization dynamics. Figure 2 shows the normalized depth profiles of B, Fe, and MgO in S-I, S-R, and S-PO.…”
mentioning
confidence: 99%
“…3 (d-f), and the estimated damping α is 0.218±0.05 for FeGa film, 0.139±0.03 for FeGaN film and 0.023±0.007 for FeGaB film, respectively. The damping of pure FeGa film is higher about ten magnitudes than most of the soft magnetic films, 2,3,5,6 and then sharply reduces to 0.023 through the additional B element. The influence of N and B contents on the damping of the film is closely related to their soft magnetic properties of the films shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Good soft magnetism and low magnetic damping factor can enhance the microwave permeability and reduce the energy loss of the thin films, and they are beneficial for the excellent high-frequency performance of the films in a minimum current density. 5,6 On the contrary, a small magnetic damping will result in a long switching time of magnetization, which is a disadvantage for the applications to achieve high operating speeds. 7 Thus, it is important for the magnetic films keeping the good soft magnetism and appropriate low damping factor.…”
Section: Introductionsmentioning
confidence: 99%
“…These CoFeB thin films exhibit a small critical current density in STT-MTJs [1] and a high speed of the DW motion in STT-DW devices [2], possibly due to the small Gilbert damping constant. Recent experiments on CoFeB thin films have shown that the Gilbert damping constant can be manipulated by either choosing appropriate materials for adjacent nonmagnetic layers [3] or adjusting the annealing process [4]. Because the magnetic properties of the films are very sensitive to the atomic mixing between the CoFeB and adjacent layers [5] during the annealing process, the annealing procedure must be optimized based on the adjacent nonmagnetic layers.…”
Section: Introductionmentioning
confidence: 99%